1998
DOI: 10.1007/bf02761772
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the molecular characterization of tryptophan hydroxylase

Abstract: The neurotransmitter serotonin has been implicated in numerous physiological functions and pathophysiological disorders. The hydroxylation of the aromatic amino acid tryptophan is rate-limiting in the synthesis of serotonin. Tryptophan hydroxylase (TPH), as the rate-limiting enzyme, determines the concentrations of serotonin in vivo. Relative serotonin concentrations are clearly important in neural transmission, but serotonin has also been reported to function as a local antioxidant. Identification of the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
1
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 136 publications
0
72
1
1
Order By: Relevance
“…4). Although neural TPH and recombinant enzymes were reportedly phosphorylated by PKA (reviewed in [38]), in the present study, we could not obtain positive evidence for PKA phosphorylation of the TPH from P-815 (Fig. 3).…”
Section: Phosphorylation Of Non-neural Tph In Vitrocontrasting
confidence: 83%
“…4). Although neural TPH and recombinant enzymes were reportedly phosphorylated by PKA (reviewed in [38]), in the present study, we could not obtain positive evidence for PKA phosphorylation of the TPH from P-815 (Fig. 3).…”
Section: Phosphorylation Of Non-neural Tph In Vitrocontrasting
confidence: 83%
“…In mammals, serotonin is synthesized from tryptophan in two steps involving L-tryptophan 5-hydroxylase and aromatic L-amino acid decarboxylase (Fig. 6) (28). Tryptophan hydroxylase belongs to a family of aromatic amino acid hydroxylases and requires iron and the coenzyme tetrahydropterin for catalytic activity (29).…”
Section: Discussionmentioning
confidence: 99%
“…This observation confirmed the repeatedly discussed hypothesis of a second TPH isoform. 12,13 Using the TPH1 sequence as a query in a screening procedure of the Human Genome Database, the group of Walter et al 11 identified a new TPH isoform which they designated as second tryptophan hydroxylase isoform (TPH2) or neuronal TPH. The expression of both isoforms is partially exclusive.…”
mentioning
confidence: 99%